Representasi Perempuan Jawa dalam Serat Wulang Putri: Analisis Wacana Kritis - Fitriana, Atin (UI Scholars Hub, 2019)
The Javanese culture has a specific perspective on the ideal figure of women. This perspective is generally manifested in the classical texts, for example, in Serat Wulang Putri Adisara. Written by Nyi Adisara. Serat Wulang Putri contains the teachings for royal daughters in living their life as Javanese women based on Javanese teachings. In this manuscript, the readers can see the women figure portrayed from the perspective of a woman writer. This paper discusses the ideal women’s discourse in Serat Wulang Putri using the approach of critical discourse analysis from van Dijk. The analysis is conducted by considering the text’s microstructure, macrostructure, and cultural context. Through the analysis, we can see the ideal discourse of Javanese women based on Serat Wulang Putri. Furthermore, the text discusses women as figures who must pay attention to their attitudes and behavior, and can control their hearts, minds, and feelings. In this case, the author uses the male point of view to describe the characteristics of ideal Javanese women. Javanese women are also described as a weak figure and must obey what men command or expect from them.